Physiological complexity of body sway during dual-task gait in faller older adults: Body sway complexity in faller older adults - Gomes de Alencar, Júlia; dos Santos Leal, Iara; Freitas e Silva, Carine; Alves dos Santos, Luan Ricardo; Alves Silva Lima, Letícia; Alves da Silva, Tarcísio Fulgêncio; Trombini-Souza, Francis (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: The impact of simultaneous cognitive demand on gait’s physiological complexity in community-dwelling older adults with and without self-reported falls is yet unknown. Objective: To analyze whether the physiological complexity of body sway during dual-task and single gait is worse in once-only fallers than in non-faller older adults. Methods: A total of 58 community-dwelling older adults aged 60 to 80 participated in this study, of whom 21 had self-reported a single fall in the previous 12 months (fallers) and 37 matched participants with no fall self-reported (non-fallers). An inertial sensor (Physilog® 5, Gait Up, Switzerland) was used to acquire the time series of the body center of mass (CoM) sway in the anteroposterior (AP), mediolateral (ML) and vertical (V) directions during single gait (ST) and the gait under dual task (DT). The composite refined multiscale fuzzy entropy method was used to calculate the physiological complexity index (CI) in a MATLAB environment. SPSS (IBM; v.25.0) was used to analyze the effects of group (Fallers vs. Non-fallers), condition (ST vs. DT), and interaction (group vs. condition), using generalized linear mixed models, with an alpha of 5%. Results: No interaction or group effect was observed for the CI. However, when comparing DT with ST, a main effect of the condition was observed for the AP direction (F = 62.394; p < .001) with a reduction of 0.53 (95% CI: -0.66 to -0.39), ML (F = 4.724; p = .034) with an increase of 0.22 (95% CI: 0.17 to 0.42), and V (F = 6.457; p = .014) with a decrease of 0.17. Conclusion: Just one fall in the previous 12 months does not deleteriously influence the body’s physiological complexity during gait under concurrent cognitive demand (dual task). On the other hand, DT significantly affects the gait physiological complexity in community-dwelling older adults.